The Empirical Nexus between Data-Driven Decision-Making and Productivity: Evidence from Pakistan's Banking Sector - Raazia Gul; Kelvin Leong; Ammara Mubashar; Mamdouh Abdulaziz Saleh Al-Faryan; Anna Sung (Cogent Business & Management, 2023)
The effective use of digital technologies to create business value has generated enormous data, and using data in decision-making is vital. Although there is growing empirical evidence in favour of a positive association between informed decision-making and firm performance in developed countries, there is little to no evidence of a large-scale study in an emerging economic context. Moreover, there has been scant empirical evidence on how DDDM affects productivity in the banking sector of developing countries. This study examined the impact of DDDM on the productivity of Pakistan's banking sector from 2016 to 2020 based on primary and secondary data collected from banks registered in Pakistan. The findings suggest that banks who adopt DDDM practices show a 4-7% increase in productivity depending on adjustment to change. We believe this study would shed light on the importance of DDDM in the banking sector of developing countries.
Keywords: 650; Banking; Data-driven decision-making; Digitalization; Productivity